An Investigation on the Factors Influencing Consumer Behavioral Intention to Adopt Broadband in Kuala Lumpur, Malaysia - Fu, Bo Yang (2014)
This research aims to investigate the factors that affect the intention of adopting broadband technology in Kuala Lumpur through the integration of the renowned framework of The Theory of planned behavior (TPB) and Unified Theory of Acceptance of Use of Technology (UTAUT) model. Self-administered questionnaires were developed and distributed around Kuala Lumpur, Malaysia targeting Malaysian at the age of 18-60. This study reflects the perception of users of broadband technology. Out of the 400 questionnaires distributed, only 389 useable questionnaires were been used for analysis purposes. The analyses were done using the SPSS and Smart PLS software and results shows all factors which are “perceived usefulness, perceived ease of use, social influence and perceived cost” were found to have a positive relationship with the intention to adopt broadband technology while the perceived usefulness shows the strongest positive relationship. The results of this research are believed to be able to provide useful insights and important implication to the government, academia, and industry to improve the adoption and diffusion of broadband technology in the future.